Appropriate knowledge of the indications for medications in use among older individuals assisted in the Jornada Científica dos Acadêmicos de Farmácia-Bioquímica - Thiago Vinicius Nadaleto Didone; Primavera Borelli; Patricia Baltrukonis Bucci Casari; Rodolfo Ribeiro de Souza; Tamara Ramos Jorge; Elvira Maria Guerra-Shinohara (Universidade de São Paulo, 2021)
This study aimed to identify variables associated with the appropriate recall of indications and the drug classes that represented the most unmatching medications (i.e., when the individual who used it had not reported any illness that matched its indications). Community-dwelling individuals aged ≥60 years using ≥1 medication, from Santa Cruz da Esperança-SP, Brazil, were home-interviewed. Logistic regression models were used to evaluate the association between the appropriate recall of the indications for all medications in use and the following: gender, age, education, individual income, living arrangement, self-perceived health, and medication number, administration, payment, and identification. Medications whose indications were inappropriately recalled were classified as matching or unmatching. One hundred seventeen individuals used an average of 5.1 (standard deviation, 3.3) medications. Sixty-one (52.1%) appropriately recalled all indications. The appropriate recall of all indications was negatively associated with the number of medications in use (e.g., individuals taking 5-6 medications were 25 times less likely to appropriately recall all indications than those taking 1-2). Antithrombotic, acid-related disorder and psychoanaleptic classes showed greater frequencies of unmatching than matching medications. Therefore, counseling the elderly about drug indications should focus on those using ≥3 medications and/or antithrombotic, acid-related disorder, and psychoanaleptic agents.